Rethinking counterfeit medical supply chains: A critical review of the current literature - Iffath U. Syed; Travis W. Milburn (Wiley, 2024)
Abstract The medical device and pharmaceutical industries include a range of drugs, machines, instruments, and apparatuses used to prevent, diagnose, treat disease and illness, or aid in rehabilitation for patients, and are expected to grow substantially in the coming years. However, they are often targets of criminal organizations who manufacture and profit from fraudulent products, infiltrating the market with counterfeit medical supply chains. In this paper, we discuss and analyze the extent and nature of this problem and make suggestions for mitigation and prevention of this worldwide challenge. Ultimately, we argue that a holistic approach is essential to addressing this problem, including the creation and dissemination of reliable and good quality data, developing healthcare systems to be more robust, establishing/enhancing intra‐ and international cooperation around this issue, and employing effective technological solutions, such as digital tracing.